1998
DOI: 10.1002/(sici)1099-1492(1998110)11:7<354::aid-nbm515>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes underlying31P MR spectral alterations in human hepatic tumours

Abstract: Magnetic resonance spectroscopy (MRS) remains the technique of choice for observing tumour metabolism non‐invasively. Although initially 31P MR spectroscopy showed much promise as a non‐invasive diagnostic tool, studies of a wide range of hepatic tumours have conclusively shown that this technique cannot be utilized to distinguish between different tumour types. This lack of specificity and sensitivity appears to be a consequence of the fact that hepatic tumours develop with a range of modalities and not as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The results from these studies and our observations suggest that up-regulation of CHKA and PCYT1A in HBV replicating cells could contribute to the HCC induced by chronic HBV infection. This notion is reinforced by the close association between CHKA overexpression and increased levels of PCho and PC, with oncogenesis, in cells, animals and patients 39 40 41 . In addition, HBV replication could induce oxidative stress through producing more reactive oxygen species (ROS) 6 42 .…”
Section: Discussionmentioning
confidence: 98%
“…The results from these studies and our observations suggest that up-regulation of CHKA and PCYT1A in HBV replicating cells could contribute to the HCC induced by chronic HBV infection. This notion is reinforced by the close association between CHKA overexpression and increased levels of PCho and PC, with oncogenesis, in cells, animals and patients 39 40 41 . In addition, HBV replication could induce oxidative stress through producing more reactive oxygen species (ROS) 6 42 .…”
Section: Discussionmentioning
confidence: 98%
“…An increase in CCT activity would therefore result in the depletion of cellular PCho levels. However, 31 P MRS has frequently demonstrated that liver tumours contain significantly increased cellular PCho levels compared with normal liver 49 . Because several enzymes, other than CCT, such as CHK and PtdCho-specific phospholipase C (PC-PLC), can increase intracellular PCho levels, these enzymes may counteract a possible depletion of cellular PCho levels by increased CCT activity in liver tumorigenesis (TABLE 1).…”
Section: Key Enzymes In Choline Metabolism In Cancermentioning
confidence: 99%
“…Furthermore, high levels of PCho have been found in tumoral cells as well as in tumour samples of cancer patients compared with the normal counterparts in breast, prostate, brain and ovarian cancer [19]–[25]. The increase in phosphoethanolamine has been also reported in transformed cells or tumor samples using MRS, although it contributes to a much lesser extent, compared with the increase of PCho, to the phosphomonoester peak [26].…”
Section: Introductionmentioning
confidence: 99%